The non-sovereign self, responsibility, and otherness : Hannah Arendt, Judith Butler, and Stanley Cavell on moral philosophy and political agency /: Hannah Arendt, Judith Butler, and Stanley Cavell on moral philosophy and political agency. (2016) - Kelz, Rosine Judith, 1981-
No abstract available